PENGARUH KEBIJAKAN DIVIDEN, GROWTH DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Atika, Atika Wulandari (Politeknik Ubaya, 2026)
This study aims to analyze the effect of dividend policy, company growth, and company size on capital structure (Empirical Study of Agriculture Sub-Sector Companies Listed on the IDX 2021-2024). Capital structure is a very important decision in financial management that can affect a company's performance and sustainability. The sample of this study was selected using a purposive sampling method with certain criteria, so that a number of companies were obtained that met the requirements during the observation period. The data used for research is secondary data obtained from annual financial reports published by the IDX. The analysis method used is multiple linear regression with the help of statistical software. The result shows that dividend policy has a significant effect on capital structure, while firm growth and firm size variables show different effects on capital structure. These findings provide implications for company management in making decisions related to funding policies, as well as for investors in considering the company's financial structure in making investment decisions.